Comparison of bacterial counts in expressed breast milk following standard or strict infection control regimens in neonatal intensive care units: compliance of mothers does matter. Issue 3 (March 2016) - Haiden, N.; Pimpel, B.; Assadian, O.; Binder, C.; Kreissl, A.; Repa, A.; Thanhäuser, M.; Roberts, C.D.; Berger, A.
Summary: Bacterial counts in 1466 expressed breast milk (EBM) samples from women following one of two infection control regimens (standard vs strict) were investigated. Overall, 12% of samples yielded Gram-negative bacteria, with no significant differences between the standard [11.9% (94/788)] and strict [12.1% (82/678)] regimens ( P  = 0.92). Significantly more samples were contaminated when expressed at home (standard regimen home/hospital: 17.9% vs 6.1%; strict regimen home/hospital: 19.6% vs 3.4%; P  < 0.001). Bacterial contamination of EBM was not associated with the regimen, but was associated with the location of breast milk expression. Attempts to improve personal hygiene during milk collection seem to be of limited value. Good hygiene of collection and storage equipment is likely to be the most important way to ensure the microbiological quality of EBM.